Isolation of an immunodominant viral peptide that is endogenously bound to the stress protein GP96/GRP94. - Nieland, T J (1996)
Heat shock protein gp96 primes class I restricted cytotoxic T cells against antigens present in the cells from which it was isolated. Moreover, gp96 derived from certain tumors functions as an effective vaccine, causing complete tumor regressions in in vivo tumor challenge protocols. Because tumor-derived gp96 did not differ from gp96 isolated from normal tissues, a role for gp96 as a peptide carrier has been proposed. To test this hypothesis, we analyzed whether such an association of antigenic peptides with gp96 occurs in a well-defined viral model system. Here we present the full characterization of an antigenic peptide that endogenously associates with the stress protein gp96 in cells infected with vesicular stomatitis virus (VSV). This peptide is identical to the immunodominant peptide of VSV, which is also naturally presented by H-2Kb major histocompatibility complex class I molecules. This peptide associates with gp96 in VSV-infected cells regardless of the major histocompatibility com- plex haplotype of the cell. Our observations provide a biochemical basis for the vaccine function of gp96.